The Reproduction of Javanese Ethnic Identity among Migrant Javanese Communities through Janengan Art in Kebumen Village, Lampung - Nur Julian Majid; Chuna Kafia Dilla (Warisan: Journal of History and Cultural Heritage, 2025)
This article examines the role of Janengan performing art in reproducing Javanese ethnic identity among Javanese migrant communities in Kebumen Village, Lampung. Within a multiethnic social setting and migratory space, Janengan is understood not merely as an Islamic-Javanese religious expression but as a cultural practice that actively sustains ethnic continuity. The study addresses how Janengan functions as a medium for maintaining and renegotiating identity in a context marked by cultural interaction and social mobility. Employing a qualitative approach grounded in cultural ethnography and oral history, data were collected through participant observation, in-depth interviews, and literature review. The findings reveal that Janengan reproduces ethnic identity through the consistent use of the Javanese language, collective performance patterns, intergenerational transmission of religio-cultural values, and the reinterpretation of symbolic elements such as sajen. At the same time, it serves as a space for social solidarity and adaptive negotiation of Islamic-Javanese identity within a multiethnic environment. The article argues that Janengan operates as a dynamic cultural strategy through which Javanese migrants preserve and reconstruct their ethnic identity in migratory settings.